Journalism as a Weapon: The Life of Patrick John Booth - Hollings J (Asia Pacific Media Network in association with Tuwhera at Auckland University of Technology)
Many countries have their Watergate moment, a scandal that envelopes not only mystery, intrigue, and human tragedy, but also something bigger, some kind of challenge to a country’s deepest beliefs about itself. What the US journalism scholar Michael Schudson called a country’s central moral values. For New Zealand, a good case could be made that our Watergate moment was the Thomas case. Like Watergate, it revealed ugly truths about corruption within some of our most respected institutions, and investigative journalism played a central role. Like Watergate, it was also a collective loss of innocence, and opened a very deep wound.
Keywords: investigative journalism; journalist; New Zealand; obituary; Pat Booth; Watergate; 1902 Film, Television and Digital Media; 1903 Journalism and Professional Writing; 2001 Communication and Media Studies